2019
DOI: 10.7567/1347-4065/ab5d66
|View full text |Cite
|
Sign up to set email alerts
|

Channel thickness-dependent mobility degradation in planar junctionless transistors

Abstract: Electrical characteristics of junctionless transistors (JLTs) with varying Si thickness (tsi), were discussed in detail with consideration to maximum depletion width (Dmax), threshold voltage (Vth) and mobility degradation caused by a transverse electric-field. The tsi significantly influences both partially depleted operation and bulk conduction, accompanied by noticeable variation in Vth and mobility degradation. Our studies provide important information for a better understanding of the operation mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The g m shoulder and d g m /d V g peaks are not present in Figure b,c, although the estimated N d_eff ≈ 8 × 10 18 cm –3 at V gb = 80 V (see also Figure S3) is similar to a highly doped value in a typical JLT channel. , Previous studies have shown that unique properties such as the g m and d g m /d V g features are strongly influenced by the parasitic series resistance and channel geometry. …”
Section: Results and Discussionmentioning
confidence: 71%
“…The g m shoulder and d g m /d V g peaks are not present in Figure b,c, although the estimated N d_eff ≈ 8 × 10 18 cm –3 at V gb = 80 V (see also Figure S3) is similar to a highly doped value in a typical JLT channel. , Previous studies have shown that unique properties such as the g m and d g m /d V g features are strongly influenced by the parasitic series resistance and channel geometry. …”
Section: Results and Discussionmentioning
confidence: 71%
“…16 Bulk conduction-based multilayer MoS 2 transistors exhibit less mobility degradation at a higher V g , as is also true of JLTs. 5,17 As V gt increases, so too does g m , reaching a maximum before being degraded by enhancement of the transverse E-field by the gate bias. The degradation is more severe for thin than thick t MoSd 2 (blue curve in Figure 3e) because the bulk neutral:surface accumulation channel ratio becomes lower as the MoS 2 structure becomes thinner.…”
Section: ■ Results and Discussionmentioning
confidence: 99%